Effect of Person-Job Fit And Training On Employee Performance With Job Satisfaction as A Mediating at BSI KC. Palopo - Sarmila Ramadhani soloweno; Salju Salju; Indra Kusdarianto (Perkumpulan Dosen Muda (PDM) Bengkulu, 2026)
Purpose: This study aims to examine the direct effects of Person-Job Fit and Training on Employee Performance, their effects on Job Satisfaction, and to assess the mediating role of Job Satisfaction in the relationships among these variables. Methodology: This research employs an explanatory quantitative approach with a cross-sectional design. The study was conducted at BSI KC Palopo. The population consists of all permanent employees, totaling 31 individuals, who were selected as the sample using a census technique. Data were collected using a questionnaire. The data analysis technique applied is Structural Equation Modeling based on Partial Least Squares (SEM-PLS). Result: The results show that Person-Job Fit has a positive and significant effect on Employee Performance, while Training does not have a direct effect on Employee Performance. Person-Job Fit also does not have a significant effect on Job Satisfaction, whereas Training has a positive and significant effect on Job Satisfaction. Job Satisfaction has a positive and significant effect on Employee Performance. Findings: Job Satisfaction does not mediate the relationship between Person-Job Fit and Employee Performance, but it significantly mediates the effect of Training on Employee Performance. Novelty: These findings provide empirical insights for the management of BSI KC Palopo in formulating recruitment, placement, and sustainable human resource development policies. Originality: This study integrates Person-Job Fit and training into a single model, with job satisfaction as a mediating variable, in the context of post merger at BSI KC Palopo. Research gap: The research gap addressed in this study lies in the limited quantitative integration of Person-Job Fit and training models, as well as the scarcity of studies in Islamic banking in the post-merger context. In conclusion, employee performance improvement is achieved through two pathways: first, Person-Job Fit directly enhances performance through capability without influencing satisfaction; second, Training improves performance indirectly through Job Satisfaction as a full mediator. Type of paper: Empirical Reasearch paper.